Integrated Mechanical Pulse Jet Coolant Delivery System Performance for Minimal Quantity Lubrication - Sapian, Nik Fazli; Omar, Badrul; Abd Shukor, Mohd Hamdi (International Journal of Integrated Engineering, 2010)
Minimum quantity lubrication (MQL) machining is one of the promising solutions to the requirement for decrease in cutting fluid consumption. This research describes MQL machining in a range of lubricant consumption 2.0ml/h, which is 10–100 times smaller than the consumption usually adopted in industries. MQL machining in this range is called pulse jet coolant delivery system in this research. A specially designed system was used for concentrating small amounts of lubricant onto the cutting interface. The performance of concentrated spraying of lubricant in pulse jet coolant delivery system design was compared with that of current ‘Pulse Jet MQL’ systems. The concentrated spraying of lubricant with a specially designed of system was quite effective in increasing tool life in the pulse jet coolant delivery system range.